Mediatisation Dynamics and Broadcast News Selection Approaches in Nigeria During the Covid-19 Era - Sam, Godwin; Obong, Ubong Andem; Shem, Woyopwa (International Journal of Humanities, Education, and Social Sciences, 2024)
This study examines how the dynamics surrounding mediatisation of COVID-19 narratives significantly impacted broadcast news selection among broadcast media professionals in Nigeria. It conceptually expounds on certain influences that mediatisation dynamics exert on broadcast news stories especially on how they were chosen, framed, and presented to the public. The theoretical foundation of this paper is provided by the Media System Dependency and Mediatisation theories. The study employs Hjarvard, Mortensen, and Eskjaer’s (2015) typologies of media dynamics: amplification, framing, performance avenues, and co-structuring to relate how mediatisation influences broadcast news selection. The study revealed that amplification entails the media’s power to magnify event, focusing predominantly on the negative aspects of the pandemic, such as death tolls and infection rates, which aligns with the typical newsworthiness criteria favouring the extraordinary and negative. Conversely, framing and performance avenues align with the broadcast media’s ability to shape how the pandemic was perceived by selecting terminology and emphasising specific issues. This includes sensitising the public on preventive measures and providing a platform for various stakeholders to communicate their actions. Co-structuring explores how the broadcast media, often controlled by the elite, influence the public agenda and prompt actions from authorities. The paper concludes that broadcast media not only influence society but are also influenced by the concept of mеdiatisation, acknowledging the vital role they play in providing information for societal well-being.